2015
DOI: 10.1515/cmble-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among IL-6, LDL cholesterol and lipid peroxidation

Abstract: Previous studies evidenced a significant reduction in serum cholesterol levels during an episode of acute inflammation. The aim of the present study was to verify the hypothesis of a regulatory role of cytokines through an in vitro model that simulates a situation of vascular inflammation and high levels of LDL or lipoperoxides. Human microvascular endothelial cells-1 were used in all experiments. The cells were exposed for 24 h to increasing doses of LDL, oxidized lipoprotein, and 8-isoprostane (in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
(46 reference statements)
2
25
1
1
Order By: Relevance
“…Mechanistically, it is unclear what factor(s) may mediate the disconnect between circulating LDL concentration and atherogenesis in this subgroup of RA patients. Inflammatory cytokines associated with RA, such as interleukin-6, up-regulate LDL receptors and scavenger receptors for modified LDL particles on hepatocytes and macrophages, potentially leading to lower circulating LDL levels while also being proatherogenic (24,25). However, we did not observe an association of higher CRP levels or Disease Activity Scores with low LDL concentration, making these unlikely to be mediators of the associations we observed.…”
contrasting
confidence: 67%
“…Mechanistically, it is unclear what factor(s) may mediate the disconnect between circulating LDL concentration and atherogenesis in this subgroup of RA patients. Inflammatory cytokines associated with RA, such as interleukin-6, up-regulate LDL receptors and scavenger receptors for modified LDL particles on hepatocytes and macrophages, potentially leading to lower circulating LDL levels while also being proatherogenic (24,25). However, we did not observe an association of higher CRP levels or Disease Activity Scores with low LDL concentration, making these unlikely to be mediators of the associations we observed.…”
contrasting
confidence: 67%
“…They confirmed that interleukin-6 (IL-6) enhances LDL receptor activity in the liver during the inflammatory response, subsequently increasing the elimination of circulating LDL-C. Thus, the acute inflammatory response in patients with ACS may increase the clearance of LDL-C, leading to a decrease in the circulating LDL-C concentration and affecting the accuracy of risk prediction (Lubrano et al, 2015). Determination of ceramide levels using a high-throughput methodology such as LC-MS/MS is efficient and convenient.…”
Section: Discussionmentioning
confidence: 85%
“…Overall, these mechanisms represent the basis for the correlation between dysregulation of eNOS/iNOS enzymes induced by high levels of oxLDLs internalization, LOX-1 overexpression, and inflammation of vascular tissues, leading to atherosclerosis development and progression (Figure 1). In accordance with this hypothesis, it has been demonstrated that the increased expression of LOX-1 represents a consequence of increasing concentrations of interleukin 6 (IL-6) indicative of the development of inflammation in microvasculature [22].…”
Section: Introductionmentioning
confidence: 99%